(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2025)
Context: Nephrolithiasis is a common condition that affects many people, especially those in their working years. The incidence of this condition is increasing and varies greatly throughout the world’s areas. In order to determine the chemical make-up of kidney stones, the current investigation was carried out. Procedures and Supplies: For this study, 54 individuals with renal stones were chosen. The samples were first swabbed to check for microbes, then rinsed in deionized water and allowed to dry. A variety of morphological traits, such as form, color, and texture, were noted. To determine how opaque the stones were, they were X-rayed. Using a scalpel, the kidney stone’s core and surface parts were sliced. In order to obtain a fine, uniform powder for qualitative measurement of different components, it was pounded using a pestle and mortar. Thirty men and twenty-four ladies made up the 54 patients. The chemical composition varied among the participants: 3 men and 2 females tested positive for inorganic compounds, 6 men and 4 females for carbonate, 4 men and 3 females for oxalate, 6 men and 5 females for phosphate, 3 men and 3 females for ammonia, 2 men and 3 females for uric acid, 4 men and 3 females for magnesium, and 2 men and 3 females for organic compounds. (P> 0.05) The disparity was not statistically significant. There were 5 males and 3 females with a sterile bacterial profile, 7 males and 6 females with a Proteus profile, 2 males and 2 females with candidain, 1 female with P aeruginosa, 2 males and 1 female with Citrobacter diversus, 2 males and 1 female with Citrobacter Freudenreichii, 6 males and 7 females with Enterobacter species, 1 male and 1 female with staphylococcus aureus, and 5 males and 2 females with contaminated results. (P> 0.05) The disparity was not statistically significant. In sum: Patients most often had Proteus spp. infections, which may result from poor urine drainage and cause persistent UTIs, as shown by the presence of MgNH4 PO4 (struvite) stones in their kidneys. Important terms: phosphate, Citrobacter diversus, and nephrolithiasis.